2011
DOI: 10.1111/j.1600-6143.2011.03467.x
|View full text |Cite
|
Sign up to set email alerts
|

Donor-Directed MHC Class I Antibody Is Preferentially Cleared from Sensitized Recipients of Combined Liver/Kidney Transplants

Abstract: For patients with chronic renal and liver diseases, simultaneous liver and kidney transplantation (SLKT) is the best therapeutic option. The role of a pretransplant donor-specific antibody (DSA) in SLKT is unclear. We report the results of a retrospective review from 7/08 to 10/09 of SLKT at our institution. Monitoring of DSA was performed using single antigen bead assay. Between 7/08 and 10/09, there were six SLKT who had preformed DSA and positive XM (four class I and II DSA, one class I DSA only, one class … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 28 publications
6
87
0
Order By: Relevance
“…In our experience, the preexisting DSAs were cleared from the circulation within a week of the transplant in 90% of presensitized recipients. 24 This mopping effect of the liver appears to be more effective against class I HLA antibodies, 52 possibly because of the higher levels of class Why a minority of cross-match-positive patients do not clear preexisting circulating antibodies, whether this can be predicted at the time of transplantation, and whether these antibodies will lead to graft dysfunction in time remain unknown. In contrast, the development of de novo HLA antibodies after liver transplantation may be easier to predict.…”
Section: Possible Mechanism Of Donor-specific Human Leukocyte Antigenmentioning
confidence: 99%
“…In our experience, the preexisting DSAs were cleared from the circulation within a week of the transplant in 90% of presensitized recipients. 24 This mopping effect of the liver appears to be more effective against class I HLA antibodies, 52 possibly because of the higher levels of class Why a minority of cross-match-positive patients do not clear preexisting circulating antibodies, whether this can be predicted at the time of transplantation, and whether these antibodies will lead to graft dysfunction in time remain unknown. In contrast, the development of de novo HLA antibodies after liver transplantation may be easier to predict.…”
Section: Possible Mechanism Of Donor-specific Human Leukocyte Antigenmentioning
confidence: 99%
“…Thus, the liver offers immunologic protection against AMR of the kidney graft. Recent studies, however, suggest that the liver may not be completely protective [14]. Preformed donor-specific antibodies have been reported to promote AMR, and in a large analysis of over 2,484 CLKT recipients, pre-sensitization had a negative impact on survival of both the patient and the kidney graft [12].…”
Section: Immunological Aspectsmentioning
confidence: 99%
“…Mendes et al [174] reported on a single center experience of emergency ABO-I LT in 10 patients with severe hepatic failure, immediately leading to death without intervention. Plasmapheresis and IVIg were implemented for immune modulation before and after LT. At a mean follow-up of 19.6 mo post-LT, 5 of these [150] LT n = 1; post-LT, after detection of AMR Plasmapheresis, rituximab Intermittent decrease of Bili, liver enzymes and DSAs'; no survival Dar et al [151] SLKT n = 6; pre-and post-LT desensitization -Survival rate 83.3% Kozlowski et al [142] LT n = 3; post-LT, after detection of AMR Plasmapheresis, rituximab Transient decrease of Bili, yGT and DSAs' in 2 patients; survival rate 33.3% Koch et al [153] SLKT n = 1; post-LT, after liver function deterioration and detection of DSAs'…”
Section: Ivig and Abo Incompatible Ltmentioning
confidence: 99%
“…studies of desensitization or treatment, decreasing levels of cytotoxic antibodies and improved allograft function (Table 4) were reported [142,[149][150][151][152][153][154][155] . Well-designed studies on this subject are needed.…”
Section: No Of Patients Receiving Cmvig Efficacy Of Cmvig On Immunolmentioning
confidence: 99%